ANALYSIS OF RAMADHAN EFFECT TOWARD MARKET RETURN AND TRADING VOLUME IN INDONESIA SHARIâ€™AH COMPLIANCE INDEX - MJU, CALVIN B1024161021 (Jurnal Manajemen Update, 2020)
ABSTRACT This research is an event study that aims to find out the effects arising from the month of Ramadan, on the Indonesian Sharia Stock Index on the Indonesia Stock Exchange for the period of 1435H to 1439H, using indicators of market returns and trading volume. This study uses secondary data in the form of daily stock index prices and daily trading volume of the Indonesian Sharia Stock Index (ISSI) with a total of 1186 days from 1435H to 1439H. The statistical test used to test the hypothesis is a non-parametric test, because the data used are not normally distributed. The results of the T-test on market returns between 1435H and 1439H are known that there is no significant difference in market return between the month of Ramadan and other month. The results of T-test on the trading volume between 1435H and 1439H, it was found that there were significant differences which meant the market responded to the event. The results of the study prove that market returns do not have significant differences due to the stable index value on Indonesian Islamic stocks. However, the trading volume has a significant difference.Â Keywords: Ramadhan, Ramadhan Effect, Market Return, Trading Volume, Index of Indonesia Shariâ€™ah ComplianceÂ REFERENCES Al-Ississ, M. 2015. The Holy Day Effect. Retrieved January 2, 2016 Alrashidi, F., Ahmed, M, Beneid, F. 2014.The Calendar Impact and Trading Behavior: an Empirical Evidence From Around the Globe. International Business & Economics Research Journal 13(5), 1025-1032. Ashari, Ikhwan. 2018. Analisis Peristiwa Ramadhan Dibalik Abnormal Return Saham pada Emiten-Emiten yang Tergabung di Indeks SRI-Kehati (Tahun 1432H â€“ 1438H). Skripsi Dipublikasikan. Malang: Fakultas Ekonomi Universitas Negeri Malang BiaÅ‚kowski, J., Etebari, A, Wisniewski, T. P. 2012.Fast Profits: Investor Sentiment and Stock Returns During Ramadan. Journal of Banking & Finance 36, 835845. Dewi, S.M.F., Gumanti, A.T., Singgih, M. (2014). â€œKonsistensi Efek Ramadhan Dalam Waktu dan Periode Yang Berbeda Pada Saham-Saham Pembentuk ILQ45 di Bursa Efek Indonesiaâ€. Jurnal Manajemen dan Usahawan Indonesia, 43 (4): 300-315. Garkaz, M., Hazini, N., Azimi, J. (2014). â€œEffect of Ramadan Month on the stock price, trade volume and index of Techran Stock Exchange in the minerals and mining industryâ€. International Journal of Scientific Management and Development, Vol.2 No.10, 550-554. George M. Frankfurtera, Elton G. Mcgoun (2001). "Anomalies in Finance What Are They and What are They Good For?" International Review of Financial Analysis, 10, p. 22. Hasbullah, F., Masih, M. (2016).â€Fast Profit in a fasting month? A markov regime switching approach in Ramadan effect on stock marketsâ€ MPRA Paper No. 72149, posted 22 June 2016. Iqbal, M. S., Kouser, R, Azeem, M. (2013). Conventional and Islamic Anomalies in Karachi Stock Exchange. Retrieved December 02, 2015, From http://www.sci-int.com/pdf/132487349256-999â€”1007Rehana%20kausarManuscript%20BZ%20Uni.pdf. Jogiyanto (2010). Studi Peristiwa :â€œMenguji Reaksi Pasar Modal Akibat Suatu Peristiwaâ€. Yogyakarta : BPFE. Junizar, Muhammad Luky, Aditya Septiani (2013). â€œPengaruh Pengumuman Pembelian Kembali Saham (Buy Back) Terhadap Respon Pasar: Studi pada 59 Perusahaan yang Terdaftar di Bursa Efek Indonesia (BEI)â€, Jurnal Akuntansi Diponegoro, Vol. 2, No. 3, 2013. Junaid et al. â€œReaksi Abnormal Return dan Trading Volume Activity Terhadap Ramadhan Effectâ€. Research Journal. Jayen B. Patel (2008), â€œCalendar Effects In The Indian Stock Marketâ€, International Business & Economic Research Journal, Volume 7, Number 3, March 2008, pp. 61-70. Kayser, S. Md., Hassan, H. Md. (2019). â€œRamadan Effect on Stock Market Return and Trade Volume: Evidence from Dhaka Stock Exchange (DSE)â€™. Research Article, Cogent Economics & Finance (2019), 7: 1605105. Klesov Andriy (2008), â€œCalendar Effects on Stock Market: Case of Selected CIS and CEE Countriesâ€, A thesis from National University â€œKyiv-Mohyla Academyâ€ Masterâ€™s Program in Economics 2008. Price Water House Coopers, (2009). Shariah-compliant funds: a whole new world of investment. Perez, A.G. (2017), â€œMonday Effect in The Chinese Stock Marketâ€, International Journal of Financial Research, Volume 9, No.1;2018. Priyansah, A.R. (2013), â€œAnalisis Pengaruh Bulan Ramadhan Terhadap Pasar Modal di Indonesia Pada Indeks Harga Saham Gabungan (IHSG/0 Periode Januari 2006 â€“ Desember 2011â€, Research study. Rusmiyati, A.,Yusniar, W.M., Juniar, A. (2016). â€œPengaruh Bulan Ramadhan Terhadap Return Pasar Saham di Bursa Efek Indonesia (1425H - 1434H)â€. Jurnal Wawasan Manajemen , Vol. 4, Nomor 1, Febuari 2016. Saputra Dwi Rian (2018). â€œPengaruh Ramadan Effect Pada Return dan Volatilitas di Bursa Efek Indonesiaâ€ Jurnal Penelitian. Seung-Chan Park, Moskalev, A.S. (2010) â€œThe 52-Week High And The January Effectâ€, Journal of Busniess & Economics Research, Volume 8, Number 3, March 2010, pp. 43-58. Sumiyana (2008), â€œDay of The Week & Monday Effect: Fenomena Yang Terbuktikan Tidak Konsisten di Pasar Modal Indonesiaâ€, Universitas Gajah Mada, Journal Manajemen Teori dan Terapan, Tahun 1, no.1, April 2008 Trihadmini, N. (2011). Contagion dan spillover effect Pasar Keuangan Global Sebagai Early Warning System. Jurnal Ekonomi dan Pembangunan Indonesia, Vol. 11 No. 2. 60 Thaler, H.R. (1987), â€œAnomalies, The January Effectâ€, Economic Perspective, Volume 1, Number 1, 1987, pp 197-201 Uyanto, Stanislaus S. â€œPedoman Analisis Data dengan SPSSâ€. Edisi Ketiga, Graha Ilmu, Yogyakarta, 2009 Winkasari et al (2019). â€œAnalisis Abnormal Return Saham Bulan Ramadhanâ€. AKUNTABEL16(1),201969-80 http://journal.feb.unmul.ac.id/index.php/AKUNTABEL W Kesuma, A.M. (2017). â€œEfek Ramadhan Terhadap Abnormal Return dan Trading Activity Volume Pada Perusahaan Yang Masuk ke Dalam Jakarta Islamic Index di Bursa Efek Indonesia Periode 2011-2017â€. Research Study.